Suspended sovereignty: civil disobedience, uncivil disobedience and appropriation of public space - Cristiá , Felix Alejandro (Revista de Filosofía, 2024)
This essay focuses on the conditions of possibility that favor the appropriation of public space as a form of active political participation in cities under democratic systems. The research stance is circumscribed within the political philosophy of the dissociative aspect of the social, so the notion of the public in relation to space is analyzed from the confrontation that occurs when the members who share the uses of space in cities disagree, disobey or oppose the power that governs over it. In this way, the public space, and its ability to be appropriated, is constitutive of the possibilities of change and political participation.